Coffee and tea consumption on the risk of osteoporosis: a meta-analysis - Li, Wopei; Xie, Yujiao; Jiang, Lei (Frontiers in Nutrition, 2025)
ObjectivesThis meta-analysis aims to quantify the relationship between coffee and tea consumption and the risk of osteoporosis and explore whether such consumption positively or negatively impacts this risk, thereby providing a scientific basis for understanding the effects of coffee and tea on bone health.MethodsWe systematically searched PubMed, the Cochrane Library, and Embase for observational studies published up to November 5, 2024, using medical subject headings (MeSH) and keywords related to “osteoporosis, tea, and coffee.” Statistical analyses were conducted using Stata software version 14.0. A fixed-effects model was used when heterogeneity was low (I2 ≤ 50% and p > 0.1). A random-effects model was used for greater heterogeneity (I2 > 50%). Publication bias was assessed using funnel plots and Egger’s regression tests.ResultsThis meta-analysis included 14 observational studies comprising 562,838 participants published between 2008 and 2024. The pooled analysis showed that coffee consumption is significantly associated with a reduced risk of osteoporosis (odds ratio [OR] = 0.79, 95% confidence interval [CI]: 0.73–0.84, I2 = 28.9%, p < 0.05). Tea consumption also demonstrated a protective effect, with a lower risk of osteoporosis (OR = 0.75, 95% CI: 0.62–0.91, I2 = 80.4%, p < 0.05). Subgroup analysis revealed that high-frequency coffee consumption (more than one cup per day) was associated with a greater reduction in osteoporosis risk (OR = 0.83, 95% CI: 0.74–0.93, p = 0.001) compared to low-frequency consumption (less than one cup per day), which showed no statistically significant reduction (OR = 0.86, 95% CI: 0.68–1.07, p = 0.171). Similarly, high-frequency tea consumption (more than four times per week) exhibited a slightly stronger protective effect against osteoporosis compared to low-frequency consumption (OR = 0.82, 95% CI: 0.70–0.97, p = 0.02).ConclusionThis meta-analysis suggests that long-term coffee and tea consumption is associated with a reduced risk of osteoporosis. Moreover, a higher frequency of consumption within a moderate range appeared to enhance the protective effect against osteoporosis.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024612101, PROSPERO CRD42024612101.